Endemism and taxonomic complexity of the genus Chaptalia (Asteraceae) in the Caribbean : I: Introduction and morphology - Katinas, Liliana (2014)
The Caribbean contains a system of islands east of Central America with a high number of endemic taxa. Some of those taxa, such as the genus Chaptalia (Asteraceae) are taxonomically complex. Thirty-one species of Chaptalia were described for the Caribbean, 28 of them supposedly being endemic. In this first part of the revision, we present the background and discuss the morphological characters of the various species and the endemism in the Caribbean Islands.